Implementation of Feeding Guidelines Hastens the Time to Initiation of Enteral Feeds and Improves Growth Velocity in Very Low Birth-Weight Infants. (April 2017) - Culpepper, Christine; Hendrickson, Kendra; Marshall, Susan; Benes, Jessica; Grover, Theresa R.
Abstract : Background: Growth and nutrition are critical in neonatal care. Whether feeding guidelines improve growth and nutrition and reduce morbidity is unknown. Purpose: Feeding guidelines for very low birth-weight (VLBW) infants were implemented in our neonatal intensive care unit (NICU) to start and achieve full enteral feeds sooner, and increase weight gain over the first month. Methods: Feeding guidelines for VLBW infants were implemented in January 2014, stratified by birth weight (<750, 750-1000, and 1000-1500 g). After trophic feedings, enteral feedings were advanced by 20 to 30 mL/kg/d. Data were analyzed for 2 years prior (baseline) and 6 months after (guideline) guidelines were implemented and included days to initiation of enteral feeds, days on total parenteral nutrition (TPN), and weight gain over the first month. Potential concomitant factors that could affect feeding tolerance were examined including indomethacin or dopamine treatment, delivery room cardiopulmonary resuscitation, and growth restriction. Results: A total of 95 infants with a birth weight of less than 1500 g were included (59 baseline and 36 guideline). Days to start enteral feeds decreased by 47% ( P < .01) and days on TPN decreased by 25% (16 days vs 11 days; P < .01). Weight gain over the first month of life increased by 15% ( p < .05). Dopamine and indomethacin use decreased during the study period, and small for gestational age infants were overrepresented in the guideline group. Implications for Practice/Research: Establishment of feeding guidelines for VLBW infants in our NICU reduced the days to start feeds and days on TPN while increasing weight gain over the first month. Improving growth and nutrition and reducing need for TPN in this vulnerable population may ultimately prevent infection and improve neurodevelopmental outcomes.